The overarm-throwing pattern among U-14 ASA female softball players: A comparative study of gender, culture, and experience - Petranek, L. J.; Barton, G. V. (Research Quarterly for Exercise and Sport, 2011)
A developmental description of overarm-throwing characteristics of U-14 female ASA softball players is presented here. Comparisons were made between these athletes and teens of similar age in the United States (Runion, Roberton, & Langendorfer, 2003) and in Germany (Ehl, Roberton, & Langendorfer, 2005). A majority of the softball players demonstrated the most advanced developmental levels for the backswing, foot, humerus, and forearm components. Seventy percent (n = 26) demonstrated a Level 2 trunk, while 30% (n = 11) demonstrated a differentiated trunk, Level 3. The average throwing velocity was 62.58 ft/s (19.07 m/s). Comparisons were made to girls with less throwing experience in the United States (Runion et al.) and Germany (Ehl et al.); the softball players threw with greater velocity (9.12 ft/s [2.77 m/s]and 15.89 ft/s [4.84 m/s], respectively) and demonstrated superior trunk, humerus, and forearm actions. The boys from both countries threw the ball faster than the softball players. Significant chi-square analyses found the softball players had superior humeral actions (Level 3) compared to the German boys and superior forearm actions (Level 3) compared to both groups of boys. Experience seems to have an impact when comparisons among girls are made; yet, explanations for differences seen between boys and girls still remain unclear and warrant further research.